White matter integrity alterations in young healthy adults reporting childhood trauma: A diffusion tensor imaging study. (December 2013) - Lu, Shaojia; Wei, Zhaoguo; Gao, Weijia; Wu, Weiwei; Liao, Mei; Zhang, Yan; Li, Weihui; Li, Zexuan; Li, Lingjiang
Objective: To date, insufficient studies have focused on the relationship between childhood trauma and white matter integrity changes in healthy subjects. The aim of the present study was to explore the potential effects of childhood trauma on white matter microstructural changes by using voxel-based diffusion tensor imaging (DTI) to examine alterations in fractional anisotropy (FA) values in a group of young healthy adults. Methods: A total of 21 healthy adults with a history of childhood trauma exposures and 21 age- and sex-matched individuals without childhood trauma were recruited in the present study. The Childhood Trauma Questionnaire was used to assess five aspects of childhood trauma exposures. DTI data were obtained on a Philips 3.0-Tesla scanner. Voxel-based analysis was conducted to compare white matter FA values between groups. Results: Adults with self-reported childhood trauma experiences showed decreased white matter FA values in the genu and body of the corpus callosum and the left occipital fusiform gyrus ( p < 0.001 uncorrected, voxel > 100). There was no significant difference in FA values between individuals with single and multiple childhood trauma exposures at the defined threshold. Conclusion: Our findings suggest that childhood trauma is associated with reduced microstructural integrity of the white matter in adulthood. These effects are still evident even in the absence of current psychiatric or medical symptoms, which may represent the vulnerability for developing mental disorders after childhood trauma experiences.